Intermittent hypoxia‐induced epiregulin expression by IL‐6 production in human coronary artery smooth muscle cells - Kyotani, Yoji (FEBS Open Bio, 2018)
Patients with obstructive sleep apnea (OSA) experience repetitive episodes of desaturation and resaturation of blood oxygen (known as intermittent hypoxia or IH), during sleep. We showed previously that IH induced excessive proliferation of rat vascular smooth muscle cells through upregulation of members of the epidermal growth factor family, especially epiregulin (EREG), and the erbB2 receptor. In this study, we exposed human coronary artery smooth muscle cells to IH and found that IH significantly increased the expression of EREG. IH increased the production of interleukin‐6 (IL‐6) in smooth muscle cells, and the addition of IL‐6 induced EREG expression. Small interfering RNA for IL‐6 or IL‐6 receptor attenuated the IH‐induced increase in EREG. IL‐6 may play a pivotal role in EREG upregulation by IH and consequently OSA‐related atherosclerosis.